"Kripke´s Near Miss" and Some Other Considerations On Rule Following - Castro, Rodrigo Jungmann de (Princípios: Revista de Filosofia (UFRN), 2010)
In his 1982 bookWittgenstein On Rules and Private Language, Saul Kripke maintains that Wittgenstein´s rule following considerations land us with a skeptical argument about meaning. This essay contains a short exposition of Kripke´s argument. In addition, I hold, both on textual grounds and by an appeal to some select secondary literature, that Wittgenstein offered no such skeptical argument in the Philosophical Investigations. Although Wittgenstein certainly repudiates a view of meaning based on temporally located mental states, it does not follow that there can be no meaning-grounding facts of other sorts. Although it is true that mental states, viewed atomistically, offer no sure foundation for meaning, I argue that it need not follow, pace Kripke, that no facts about an individual´s past mental life can ever make it clear that he meant ‘plus’ rather than ‘quus’ while performing any addition. For the individual´s past mental life is indeed relevant to meaning when considered in its unfolding in time. The essay further contains explorations on the very nature of the practice of following a rule and ends with a discussion of the solitary rule follower.